Benefits of infant calendar action poster to improve the compliance of growth and development monitoring - Sudiyanto Darmosubroto; Sudigdo Sastroasmoro; Rini Sekartini (Indonesian Pediatric Society, 1999)
A community based study was conducted among infants between 0-12 months old about the compliance of growth and development monitoring, with the provision of infant calendar action postern. The subjects of study residing at Cipinang Cempedak areas,Mere fonowed-up from March 1997 until March 1998. One hundred infants providedÂ· with the action postern comprised the intervention group, and 100 infants not provided with the action posters comprised the non intervention or the control group. Twenty infants of the control group and 18 infants of the intervention group dropped out because they moved out areas or didn't show up at the subsequent visit. More than half of the parents has middle income with Rp 134,832.35 â€“ Rp 1,664,733.75 per month, 75.3% the fathers were employees of private enterprises. Eighty two of the intervention group (36 male infants or 43.9% and 46 female infants or 56.1 %) and 80 of the non intervention group d (39 male infants or 48.8 % and 41 female infants or 51.2%) participated in this study. The results showed that the compliance of periodical visits of growth and development monitoring of the intervention group was significantly better than that of the control group. Other results show that the intervention group got proper feeding, had adequate nutritional status, and had complete immunizations as recommended. And sustained contraceptive practice by the mothers.